Assessing the energy benefit of using a wind turbine micro-siting model. (April 2018) - Parada, Leandro; Herrera, Carlos; Flores, Paulo; Parada, Victor
Abstract: Wind farm layouts are often designed based on simple rules that give rise to regular arrays. Several studies have stated that these arrays may not be efficient due to high wake losses for some wind directions. Recently, wind turbine micro-siting models have been compared with respect to regularly arrayed layouts. However, these studies have considered just a single regular layout configuration and a fixed number of turbines. In this paper, an approach is proposed to design highly efficient wind farms and is further compared to different configurations of regularly arrayed layouts considering different spacings and number of wind turbines. The proposed approach maximizes the power of a wind farm and efficiently incorporates the use of irregular terrain boundaries and real wind data. The proposed approach is first compared to the Horns Rev I layout. Subsequently, the proposed approach is further compared to different regular layout configurations using wind data measured at a site located in Northern Chile. The results suggest that regularly arrayed wind farms are sub-optimal and may be subjected to high wake losses, particularly for some wind directions. With the proposed approach, 4.09 % and 2.18 % higher efficiencies on average were obtained compared to aligned and staggered layouts, respectively. Highlights: The energy benefit of using micro-siting models over regular design rules is evaluated. The approach considers a micro-siting model that maximizes the power output. The approach incorporates the use of irregular terrain boundaries and real wind data. On average, 4% higher efficiencies were obtained compared to regular aligned layouts. The higher losses of regular layouts are due to a wake chain of more than 2 turbines.